Electronic and Internet Technologies in the Election Process - Щебетун, Ірина Степанівна; Щебетун, І. С.; Щебетун, Ирина Степановна; Shchebetun, Iryna S.; Нікітенко, Лілія Олександрівна; Нікітенко, Л. О.; Никитенко, Лилия Александровна; Nikitenko, Liliia O.; Писарєва, Елла Анатоліївна; Писарєва, Е. А.; Писарева, Элла Анатольевна; Pysarieva, Ella A.; et al. (Mattingley Publishing Co., Inc., 2020)
The rapid development of scientific, technical and technological developments has contributed to the transition of a large number of democratic countries to electronic political infrastructure and e-democracy tools, including the conduct of electronic elections and voting. Ukraine is no exception in which electronic and Internet technologies have a significant impact on policy relations; communication between politicians and citizens in the electoral process. Therefore, it is important to examine the impact and role of electronic and Internet technologies on Ukraine's electoral process, to compare it with the experience of foreign countries, and to analyze new opportunities for transforming the electoral process in Ukraine in line with democracy standards. The purpose of the paper is to investigate the place of electronic and Internet technologies in the electoral process, including the electoral process of Ukraine. The subject of the study is electronic and Internet technologies in the election process. As a result of the study of electronic and Internet technologies in the electoral process, we can conclude that the Internet and electronic technologies play an important role in modern electoral processes. Despite the adoption of the new Electoral Code of Ukraine, the electoral process in Ukraine needs quality changes and modernization. Besides, it is quite relevant for Ukraine to switch to electoral support with the latest information and communication technologies, since electronic and Internet technologies, if properly used, can ensure the electoral process is democratic and to improve the functioning of institutions of representative democracy in general.

Швидкий розвиток наукових, технічних і технологічних розробок сприяв переходу великої кількості демократичних країн на електронну політичну інфраструктуру та інструменти електронної демократії, включаючи проведення електронних виборів та голосування. Україна не є винятком, коли електронні та Інтернет-технології мають значний вплив на політичні відносини, спілкування між політиками та громадянами у виборчому процесі. Тому важливо вивчити вплив та роль електронних та Інтернет-технологій на виборчий процес в Україні, порівняти його з досвідом зарубіжних країн та проаналізувати нові можливості для трансформації виборчого процесу в Україні відповідно до стандартів демократії. Метою статті є дослідження місця електронних та Інтернет-технологій у виборчому процесі, включаючи виборчий процес України. Предметом дослідження є електронні та Інтернет-технології у виборчому процесі. В результаті вивчення електронних та Інтернет-технологій у виборчому процесі можна зробити висновок, що Інтернет та електронні технології відіграють важливу роль у сучасних виборчих процесах. Незважаючи на прийняття нового Виборчого кодексу України, виборчий процес в Україні потребує якісних змін та модернізації. Крім того, для України цілком доречно перейти на проведення виборів за допомогою новітніх інформаційно-комунікаційних технологій, оскільки електронні та Інтернет-технології за належного використання можуть забезпечити демократичність виборчого процесу та покращити функціонування інститутів представницької демократії загалом.

Быстрое развитие научных, технических и технологических достижений способствовало переходу большого числа демократических стран к электронной политической инфраструктуре и инструментам электронной демократии, включая проведение электронных выборов и голосования. Украина не является исключением, когда электронные и интернет-технологии оказывают значительное влияние на политические отношения, общение политиков и граждан в избирательном процессе. Поэтому важно изучить влияние и роль электронных и Интернет-технологий на избирательный процесс в Украине, сравнить его с опытом зарубежных стран и проанализировать новые возможности для трансформации избирательного процесса в Украине в соответствии со стандартами демократии. Целью статьи является исследование места электронных и Интернет-технологий в избирательном процессе, в том числе в избирательном процессе Украины. Предмет исследования - электронные и интернет-технологии в избирательном процессе. В результате изучения электронных и Интернет-технологий в избирательном процессе можно сделать вывод, что Интернет и электронные технологии играют важную роль в современных избирательных процессах. Несмотря на принятие нового Избирательного кодекса Украины, избирательный процесс в Украине нуждается в качественных изменениях и модернизации. Кроме того, для Украины весьма актуален переход на проведение выборов с использованием новейших информационных и коммуникационных технологий, поскольку электронные и интернет-технологии при правильном использовании могут обеспечить демократичность избирательного процесса и улучшить функционирование институтов представительной демократии в целом. .
Shchebetun I. Electronic and Internet Technologies in the Election Process / I. Shchebetun, L. Nikitenko, E. Pysarieva, O. Turchenko, M. Afanasieva // Test Engineering & Management magazine. – V. 83. – Mattingley Publishing Co., Inc.., 2020. – P. 6776-6784.
Keywords: electoral process; electronic technologies; Internet technologies; electronic voting; democracy; виборчий процес; електронні технології; Інтернет-технології; електронне голосування; демократія; избирательный процесс; электронные технологии; Интернет-технологии; электронное голосование; демократия; Research Subject Categories::LAW/JURISPRUDENCE